Analisis Pelaksanaan Program Peningkatan Destinasi Wisata Di Provinsi Sumatera Selatan - Gunawan, Tri; Mudasir, Mudasir; Iriani, Atrika (@-Publik: Jurnal Administrasi Publik, 2021)
The purpose of this study was to analyze the implementation of the tourism destination improvement program in South Sumatra Province. The problems that will be studied are limited transportation facilities both in quality and quantity, hindering the movement of people and tourists, as well as increasingly diverse tourism market conditions that demand a tourist destination. Although there are still obstacles related to limited means of transportation both in terms of quality and quantity, hindering the movement of people and tourists, as well as different market conditions. This study concludes that the overall implementation of the Tourism Destination Improvement Program in South Sumatra Province has been running as it should. Although in practice there are still obstacles from the limited means of transportation, both quality and quantity, hampering the mobility of both the community and tourists.